Emotional Branding Scale and Its Role in Formation of Brand Trust. Issue 2 (December 2019) - Singla, Vikas; Gupta, Gaurav
The importance of emotional branding (EB) strategy in building long-term and sustainable psychological links with consumers had been sufficiently highlighted in literature. However, very few research attempted to provide a structured tool for its measurement. This study proposed a 13-point four-factor multidimensional scale which could be used to measure EB formally. Dimensions measuring EB were derived from literature and then examined on three different brands in order to achieve a reliable and valid scale. Findings suggested brand loyalty, brand association, perceived quality and brand personality as constructs which would form the scale. The second part of the study was devoted to understand the role of these constructs in achieving ultimate goal of branding, that is, to infuse trust in consumers. A key finding suggested that emphasis on brand loyalty results in formation of trust and mitigates scepticism. Also, trust was positively and significantly impacted by brand loyalty and association, whereas a mismatch of brand personality with emotions reflected by brand could result in scepticism.